Savoir donner : les enjeux d’une définition scolaire de la philanthropie dans les pensionnats internationaux de Suisse romande - Caroline Bertron (Cahiers de la Recherche sur l'Education et les Savoirs)
This article aims at studying how philanthropic donations and charitable practices are constructed as academic knowledge in elite private schools. Swiss boarding schools are famous for welcoming cosmopolitan upper-class children from abroad. They have also been offering international curricula, and lately adopted the International Baccalaureate. By using the symbolic capital attached to alumni known to be philanthropists, these institutions provide an implicit education to charity. They also provide an explicit, academically recognized teaching of giving through community service. In this article, we examine the construction of this philanthropic knowledge at the international level (the International Baccalaureate Organization) and its local appropriation. In the very privileged boarding schools under study, as students engage in fundraising, community service leads to philanthropy. It also emerges as an elite practical knowledge, requiring technical and management skills. Finally, in Swiss boarding schools, the evolution of school curricula combined with the evolution of students’ enrollment (from Northern elites to Southern elites) question the role of charity in the formation of “new” international elites.